(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article tries to introduce the issues and challenges of the 21st century in India. Things are changing in our Education System very quickly. The world is becoming interconnected technology is continuously altering our relationship to information. Changing global conditions demand that we rethink what, but even more important, how we learn and lead. We need education for 21st century.